An extensive study of human IgE cross-reactivity of Blo t 5 and der p 5 - Kuo I.C. (2014)
Background: Dual sensitization by Blomia tropicalis and Dermatophagoides pteronyssinus mites is common in tropical and subtropical countries. The human IgE cross-reactivity between clinical important group 5 allergens, Blo t 5 and Der p 5, remains controversial. Objective: This study was undertaken to assess the levels of the IgE cross-reactivity between Blo t 5 and Der p 5 by using sera from a large cohort of asthmatic children in subtropical and tropical countries. Methods: Purified recombinant Blo t 5 and Der p 5 were produced in Pichia pastoris and tested against sera from 195 asthmatic children. The IgE cross-reactivity was examined by direct, inhibitory and competitive human IgE enzyme-linked immunosorbent assay as well as skin prick tests. Results: The Blo t 5 IgE responses were 91.8% (134 of 146) and 73.5% (36 of 49) for Taiwanese and Malaysian sera, respectively. The Blo t 5 specific IgE titers were significantly higher than those of Der p 5 (P < .02). The correlation of IgE reactivity between Blo t 5 and Der p 5 was low, and only limited cross-reactivity was observed. This was further confirmed by the dose-response inhibition studies. Skin prick tests performed on asthmatic children in Thailand also showed differential IgE response to Blo t 5 and Der p 5. Conclusion: By using a large panel of asthmatic sera and a combination of in vitro and in vivo assays, the major allergen of B tropicalis in tropical and subtropical regions, Blo t 5, exhibits low levels of IgE cross-reactivity with homologous Der p 5. These findings suggest that highly specific clinical reagents are necessary for precise diagnosis and immunotherapeutic treatment of sensitization to group 5 mite allergens.